2018
DOI: 10.1177/1934578x1801300923
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Natural Antioxidant Properties of Resveratrol

Abstract: Polyphenols, including anthocyanins, flavonoids and stilbenes, which constitute one of the most abundant and ubiquitous groups of plant metabolites, are an integral part of the human diet. Resveratrol (3,5,4'-trihydroxystilbene), a naturally occurring polyphenol produced by some plants as a self-defence agent, has an antifungal activity. Resveratrol has been found in some plants (such as grapevine, pine and peanuts) and is considered to have beneficial effects also on human health. The number of studies on res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 135 publications
(166 reference statements)
0
65
0
9
Order By: Relevance
“…CVD is associated with high cholesterol levels in the blood-in particular, low-density lipoproteins (LDL). It is widely accepted that an excessive dietary intake of saturated fats and an unhealthy diet increases cholesterol and LDL levels in the blood [15,110,163] Thus, the research by Renaud et al [12] that the French population suffered a relatively low incidence of coronary heart disease (CHD) despite the high intake of saturated fat, has sparked the interest of many researchers. The so-called "French paradox" was attributed to moderate wine consumption and its polyphenolic compounds.…”
Section: Cardiovascular Protectionmentioning
confidence: 99%
“…CVD is associated with high cholesterol levels in the blood-in particular, low-density lipoproteins (LDL). It is widely accepted that an excessive dietary intake of saturated fats and an unhealthy diet increases cholesterol and LDL levels in the blood [15,110,163] Thus, the research by Renaud et al [12] that the French population suffered a relatively low incidence of coronary heart disease (CHD) despite the high intake of saturated fat, has sparked the interest of many researchers. The so-called "French paradox" was attributed to moderate wine consumption and its polyphenolic compounds.…”
Section: Cardiovascular Protectionmentioning
confidence: 99%
“…Peanuts are among the few plant species that produce resveratrol (Lanz et al, 1990;Sobolev and Cole, 1999;Arora and Japlan, 2018). This phenolic compound is a potent antioxidant (Frankel et al, 1993) whose healing and preventive potential for many human diseases were described in some recent reviews (Colica et al, 2018;Galiniak et al, 2019). Resveratrol is also a phytoalexin that has been associated with resistance to major peanut diseases (Sobolev et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, resveratrol was isolated from several other plants, fruits, and derivatives, from grapes, wines, apples, raspberries, blueberries, pistachios, plums, peanuts, and a multitude of medicinal and edible plant species undergoing response to stress conditions [ 3 ]. Experimental and preclinical studies have shown that resveratrol has several health-promoting properties, including cardioprotective effects, chemo-preventive activity in diverse cancers, and a capacity to extend the lifespan of lower organisms [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%